Effects of dried distillers grain with solubles on nursery pig performance - Linneen, S.K.; Steidinger, M.U.; Tokach, Michael D.; DeRouchey, Joel M.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 482 pigs (initial BW of 21.9 lb) were used in a 22-d study to determine the effects of dried distillers grains with solubles (DDGS) on growth performance of nursery pigs reared in a commercial environment. Pigs were allotted to one of two dietary treatments based on corn-soybean meal and containing either 0 or 10% DDGS. There was a tendency for pigs fed the diet containing 10% DDGS to have decreased (P<0.13) ADG, compared with pigs not fed DDGS (0.95 vs. 0.88 lb/d). Overall (d 0 to 22), there were no differences in ADFI, F/G, or final weight (P>0.21). For economic analysis, the DDGS price was compared at $109, $93, or $80/ton. There were no differences in feed cost per pound of gain in diets containing DDGS at the three price levels (P>0.29). Pigs fed the diets containing 10% DDGS had a tendency for reduced (P<0.12) margin over feed cost ($0.52, $0.54, and $0.56), regardless of DDGS price ($106, $93, or $80/ton, respectively). Although only a trend for decreased ADG was observed, feeding diets containing DDGS was less economical, as measured by margin over feed costs.
Keywords: Dried distillers grain with solubles; Nursery pigs; Growth; Swine